ANALISIS SISTEM INFORMASI PENERIMAAN KAS DARI PENJUALAN TIKET BUS DI PT. ABCD - Ivan Maurits; M.Achsan Isa Al Anshori (Jurnal Ilmiah Teknik, 2023)
This research aims to analyze the information system and cash receipt procedures from bus ticket sales at PT.ABCD and evaluate the compatibility of the accounting information system and procedures applied in the company with business aspects. The research method employed is qualitative, using a descriptive analysis approach with qualitative techniques. Data collection involves preliminary surveys, field studies through interviews, and document collection. The results of the study indicate that the accounting information system and cash receipt procedures in bus ticket sales are in line with business aspects, but there are still shortcomings. Some documentation processes are not fully compliant, and certain activities are carried out without specific and continuous rules. Despite the use of computerized cash receipt systems, there are still manual processes leading to inconsistency in recording, which may potentially result in ineffectiveness during future audits.